A (des)proteção social de adolescentes privados de liberdade em contexto de violência estrutural - Staats, Laís Silva (2022)
This dissertation has as its issue the contradictions of socio-educational measures for deprivation of liverty that concern to social protection for adolescents and young people. In order to offer theoretical contributions and support to this debate, the social protection is problematized. The research carried out has qualitative nature, based on the dialectical-critical method. The as analytical categories of the method are: contradiction, totality and historicity. The explanatory categories of the reality are: social protection, adolescence and youth, deprivation of liberty and structural violence. To achieve the research purpose, a field, bibliographical and documentary research were carried out, which the data were analyzed based on the discursive textual analysis technique, according to Moraes (2003). Two interviews were carried out with professionals at the technical team that work at the Fase RS; two files of the teenagers and young people were accessed and analyzed; eleven scientific articles were selected for analysis, all in the area of Social Work, published between 2012 and 2020. The interviews with the two professionals pointed out possibilities and challenges for the materialization of social protection for adolescents and young people deprivated of liberty, which were intensified because the Covid-19 pandemic. The files of the teenagers and young people analyzed did not present records that showed articulation with social policies outside the insitution, during the application of the socio-educational measure, which demonstrates the non-materialization of the principle of the institutional incompleteness. For that matter, the interviews and records indicate the leak of social protection for adolescents and young people. Furthermore, it was identified that there is little production of knowledge in the area of Social Work regarding the research's theme, and that the publications selected for analysis point to normative advances regarding to childhood, adolescence and youth, but that do not go beyond its formality, being crossed by the reproduction of the State repressive interventions. As findings of this dissertation, the following contradictions are identified: absence-presence, protection-punishment, inside-outside, access-violation and inclusion-exclusion. These contradictions are interconnected and show structural dimensions that violate adolescents and young people through social control mechanisms. The contradiction absence-presence concerns the paradoxical role that the State assumes in the (non) promotion of social protection; the protection-punishment concerns the fine line between protection and punishment; the inside-outside and the access-violation concern the deprivation of liberty as means for accessing rights, where institutional incompleteness is not materialized, as well as the violation of these rights happens in the territory they live; and the inclusion-exclusion concerns the inclusion through the exclusion. Therefore, this dissertation highlights that adolescents and young people deprived of liberty live in a historical lack of social protection, including in the contemporaneity that is marked by the neoliberal rationality and the intensification of the conservatism.